Pengaruh Social Media Marketing Melalui Instagram Terhadap Purchase Intention (Survei pada Konsumen Pengguna Produk Mexshamall Store Tasikmalaya) - Alma Zakiah Salsabila; Ratih Tresnati (UNISBA Press, 2022)
Abstract. The purpose of this research is to find out the implementation of Social Media Marketing and Purchase Intention at Mexshamall Store, and also to discover how much impact Social Media marketing partly and concurrently has on purchase intention at Mexshamall store Tasikmalaya. The problem found in this study is that Social Media Marketing has not been able to encourage Purchase Intention at the Mexshamall Store because there are still shortcomings in the application of Social Media Marketing. The method used in this study is a survey method with a sampling technique using a probability sampling technique, and the chosen technique is simple random sampling. This type of research is descriptive verification with a quantitative approach. The population in this study are consumers who use Mexshamall Store products in Tasikmalaya. The sample taken is 100 respondents. The data analysis method used is simple linear regression analysis with the purpose of knowing the direction of the relationship between Social Media marketing and buy purpose. In this test the results state that the Social Media Marketing variable on the Mexshamall Store Purchase Intention has a significant partial and simultaneous effect. Abstrak. Tujuan dari penelitian yang telah dilakukan ini untuk mengetahui penerapan Social Media Marketing, dan Purchase Intention di Mexshamall Store, dan juga untuk mengetahui seberapa besar pengaruh Social Media Marketing secara parsial dan simultan terhadap Purchase Intention di Mexshamall Store Tasikmalaya. Masalah yang ditemukan dalam penelitian ini adalah Social Media Marketing belum mampu mendorong Purchase Intention di Mexshamall Store karena masih terdapat kekurangan dalam penerapan Social Media Marketing nya. Metode yang digunakan dalam penelitian ini yaitu metode survei dengan teknik pengambilan sampel menggunakan teknik probability sampling, dan yang dipilih yaitu teknik simple random sampling. Jenis penelitian ini ialah deskriptif verifikatif dengan pendekatan kuantitatif. Populasi dalam penelitian ini ialah konsumen pengguna produk Mexshamall Store di Tasikmalaya. Sampel yang diambil berjumlah 100 responden. Metode analisis data yang dipakai adalah analisis regresi linier sederhana yang tujuannya untuk mengetahui arah hubungan Social Media Marketing terhadap Purchase Intention. Dalam pengujian ini hasilnya menyatakan bahwa variabel Social Media Marketing terhadap Purchase Intention Mexshamall Store berpengaruh signifikan secara parsial dan simultan.